THE EMERGING TRENDS AND IMPRACTICALITIES IN ENFORCING SEC. 89, C.P.C., 1908 - R. Gomathi (International Journal of Research Science and Management, 2018)
The term law denotes the set of rules and regulations which acts as an effective means of social control. This article mainly deals about the emerging concept of Alternate Dispute Resolution, which is still at its infancy in India, though it is in vogue for more than a decade, drawing inspiration from the developed countries of the world. This article also endeavors to critically analyze the practical inabilities in implementing Sec.89 of Code of Civil Procedure Code, 1908 , where difficulties creeps out for the judges in giving the soul to the said provision and ultimately ends up with the litigant’s crying need for his justice , as ex debitojustitiae, which seems to be a farfetched one . These are discussed in light of the landmark decisions of the Apex Court in resolving the ambiguities involved in the said provision.